PENINGKATAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM (PAI) MELALUI PROGRAM SERTIFIKASI - Masitoh, Dewi (AS-SALAM, 2019)
This article aims to analyze the driving and inhibiting factors for increasing the professionalism of Islamic Education teachers after being given a certification allowance. The type of this research is Field Research, the data collection method uses interviews, documentation and observation, to check the validity of the data using triangulation techniques and the data is analyzed in three stages, namely data reduction, data presentation, and conclusions. The results showed that the increase in professionalism of Islamic Education teachers through the certification program was satisfactory, but it had not gone as expected. The certification program which aims to improve teacher professionalism and welfare has not been implemented properly. This is evident from the research findings which reveal that certified PAI teachers have not met the professional teacher criteria as expected. It is hoped that the positive contribution of this article can become a reference for similar studies in the future, and can be a reference in order to achieve teacher professionalism through the certification program.